2012
DOI: 10.1177/1758834012455838
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic options in older patients with metastatic non-small cell lung cancer

Abstract: Abstract:The increase in life expectancy, with its concomitant increase in the risk of cancer, has led to an increased incidence of lung cancer in older people. The median age at diagnosis of lung cancer is between 63 and 70 years. For a long time, there has been a pessimistic attitude by doctors, patients and their relatives and thus an undertreatment of older patients. Older patients have some specific differences compared with younger patients: more comorbidities with concomitant medications that may interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Although most RCTs were initially focused on younger adults, there is growing evidence supporting the use of chemotherapy and RT in elderly patients with advanced NSCLC [9, 2131]. The first RCT specifically focused on older patients (n=191), conducted by the Elderly Lung Cancer Vinorelbine Italian Study Group (ELVIS), found that single-agent chemotherapy, compared to supportive care, offered a survival benefit [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although most RCTs were initially focused on younger adults, there is growing evidence supporting the use of chemotherapy and RT in elderly patients with advanced NSCLC [9, 2131]. The first RCT specifically focused on older patients (n=191), conducted by the Elderly Lung Cancer Vinorelbine Italian Study Group (ELVIS), found that single-agent chemotherapy, compared to supportive care, offered a survival benefit [26].…”
Section: Discussionmentioning
confidence: 99%
“…SqCC is an aggressive subtype accounting for 25 – 30% of NSCLC cases, making it the second most common type of lung cancer [2]. SqCC is notoriously difficult to treat as patients tend to be older, present with advanced disease and have centrally located tumors [3, 4]. Smoking is strongly associated with SqCC requiring clinical attention to other comorbidities when considering therapeutic options [5].…”
Section: Introductionmentioning
confidence: 99%
“…Because of these limitations it could not be concluded that platinum-based doublet therapy should be considered as first-line treatment in patients aged >70 years of age. (3) The results of the present systematic review may be influenced by four large trials, 7,8,19,22 which may be responsible for the lack of survival benefit seen in East Asian patients. It is possible that even after pooling the data, the power may have been inadequate to detect a difference.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, a cut off has been set at 65 years of age, particularly in epidemiological studies, but this is problematic as the median age of lung cancer diagnosis is 70-71 years. 19,28 The cut off for entry into therapeutic trials is usually 70 years of age, probably because treatment may not require age-related adaptation before this age cut off; 19,28 (2) The treatment schedules differed between the included trials. Because of these limitations it could not be concluded that platinum-based doublet therapy should be considered as first-line treatment in patients aged >70 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation